BEBERAPA FAKTOR YANG MEMPENGARUHI PRAKTIK MEROKOK SANTRI DI PONDOK PESANTREN DARUT TAQWA KOTA SEMARANG - Arifiana Khoirunnisa; Priyadi Nugraha Prabamukti; Kusyogo Cahyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Trend of age smoking continues to increase in the age group of 10- 14 years and 15- 19 years. Smoking behavior is often found in school including in Islamic boarding schools. At Darut Taqwa Islamic Boarding School in the middle September- december 2017, found 24 smoking students (25%). The purpose of this study was to analyze the factors that influencing the smoking practices of students at Darut Taqwa Islamic Boarding School in Semarang City. This research was a quantitative study with a cross sectional approach. The population in this study were male students at the junior and senior high school level, the sample was taken with total sampling technique totaling 96 people. Data collection using questionnaires (questionnaire). Data analysis was carried out in univariate, bivariate and multivariate. The result showed the majority of respondents smoked (63.5%). The majority of the age in the early adolescent category are 12-16 years (68.7%) and have monthly allowance <Rp. 350,000 (56.3%). Most respondents have poor knowledge (51%), non-permissive attitudes (56.3%), Kiai (52.1%) support smoking practices and cigarettes easily accessible (55.2%). The related variables are monthly allowance (p=0.023), attitude (p=0.000), Kiai support (p=0.002) and ease of access to get cigarettes (p=0.000). The logistic regression test showed that the attitude towards smoking practice (p=0.009) was the variable that had the most significant influence of smoking practices (OR=4.408). This research is expected to be input to prevent the increasing number of adolescent smoking practices, especially students at islamic boarding school.